2019
DOI: 10.1080/1331677x.2018.1550003
|View full text |Cite
|
Sign up to set email alerts
|

Sources of export growth and development of manufacturing industry: empirical evidence from Croatia

Abstract: The article quantifies the sources of manufacturing export growth in Croatia. The research objectives are achieved by applying the constant market share method (C.M.S.) and input-output model. While the C.M.S. method quantifies the factors which explain trends in manufacturing exports, the input-output method quantifies the impacts of manufacturing exports on other domestic sectors. The obtained results show that after the E.U. accession export performance of the Croatian manufacturing industry have substantia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
1
9
0
4
Order By: Relevance
“…U recentnim empirijskim istraživanjima doma ih autora prevladava primjena klasi nog IO pristupa (Jur i , 2000;Gorjan, Lovrin evi i Mikuli , 2003;Botri , 2013). Najve i dio empirijskih istraživanja koristi kao metodološku osnovu samostalnu IO analizu (Buturac i Vizek, 2015;Lovrin evi , Buturac i Mikuli , 2015;Buturac, Lovrin evi i Mikuli , 2017;Ivandi i Šutalo, 2018;Buturac, Mikuli i Pali , 2019), dok se u novijim istraživanjima IO analiza kombinira s drugim metodama (Ke ek, Dušak i Žajdela Hrustek, 2015; Buturac, Lovrin evi i Mikuli , 2014). U ranijoj literaturi razvijena su dva glavna pristupa za analizu utjecaja pojedinog sektora na ostale sektore gospodarstva koji se temelje na IO tablicama, a pomo u kojih se može odrediti doprinos sektora ukupnom gospodarstvu.…”
Section: Uvodna Razmatranjaunclassified
“…U recentnim empirijskim istraživanjima doma ih autora prevladava primjena klasi nog IO pristupa (Jur i , 2000;Gorjan, Lovrin evi i Mikuli , 2003;Botri , 2013). Najve i dio empirijskih istraživanja koristi kao metodološku osnovu samostalnu IO analizu (Buturac i Vizek, 2015;Lovrin evi , Buturac i Mikuli , 2015;Buturac, Lovrin evi i Mikuli , 2017;Ivandi i Šutalo, 2018;Buturac, Mikuli i Pali , 2019), dok se u novijim istraživanjima IO analiza kombinira s drugim metodama (Ke ek, Dušak i Žajdela Hrustek, 2015; Buturac, Lovrin evi i Mikuli , 2014). U ranijoj literaturi razvijena su dva glavna pristupa za analizu utjecaja pojedinog sektora na ostale sektore gospodarstva koji se temelje na IO tablicama, a pomo u kojih se može odrediti doprinos sektora ukupnom gospodarstvu.…”
Section: Uvodna Razmatranjaunclassified
“…Mikuli c and Lovrin cevi c (2018) analysed import content across economic sectors in Croatia and reported the highest imported content in domestic final demand while pointing out low import dependence in Croatian industry. Buturac et al (2019) found export performance of the Croatian manufacturing industry substantially improved after accession of Croatia to EU. Therefore, the link between domestic demand for final goods and import demand might be stronger compared to a link between import demand and export supply in the cases of Croatia and Serbia.…”
Section: Research Results and Discussionmentioning
confidence: 96%
“…International competitiveness in high-technology goods is particularly essential for small and open economies, as it not only gives them the opportunity to improve their place in the international division of labour, and thus achieve faster economic growth, but it can also create a sufficient buffer against unpredictable external price shocks of labour and capital-intensive goods (Falkowski 2018;Buturac et al, 2019). Despite this fact, the trade theories are mainly focused on the effects of technology disparities (Grossman & Helpman, 1995) and not in their causes (Wolfmayr-Schnitzer, 1998).…”
Section: Research On Export Competitivenessmentioning
confidence: 99%